Sobre as águas: a tradição e a pesca artesanal em três comunidades da Reserva Extrativista Acaú-PB/Goiana-PB - Targino, Gekbede Dantas (2012)
The coastal fishing communities present several realities which always reveal a specific knowledge about their way of living. In this sense, we have tried to show, in this particular research, a reflection about the tradition in three communities located by the banks of the Goiana and Megaó Rivers, which make part of the Marine Extractive Reserve in Acaú/PB-Goiana/PE, established in 2007 and situated on the borders of Paraíba and Pernambuco. The chosen field occurred for the predominance of the small-scale fishing sector, although the insertion of new residents, undertakings, fishers from other states, impacts generated by the disordered growth, among other factors that have got in the way on the common spaces of housing, work and community sociability. Such aspects are described by the memory and tradition. In the marine and fishing sociology and anthropology we have focused on the socio-cultural changes that the estuarine who live on the border of the Goiana and Megaó Rivers have been experiencing since its constitution, mainly, the stories about the place, the work and survival strategies, the hard daily life in the tide and in the uncertain “fishing”, the social organization, the cultural manifests and the celebrations, that is, the peculiar way of life of those who outline in the fishing practice some knowledge which is typical of the traditional populations. The methodology has occurred by the participant observation, resources of life history and registers of testimonials through oral story. Besides, our observations have also aimed to contribute for the ethnography of the fishers who have been born, raised or lived for more than 10 years in the analyzed communities. The ethnography suggests an analytical and descriptive report of a traditional way of living which has been revised by the social dynamics and may, in this way, contribute for future management actions in the Unit of Conservation (Resex Acaú-Goiana). The tradition is re-elaborated and re-invented as a way of small-scale fishing resistance because of the changes and impacts lived by the fishers from Acaú-PB, Carne de Vaca-PE, São Lourenço Village-PE, and this resistance is penetrated in the social and fishing productions and in the way of being and doing the artisanal fisher.